Evaluating IL-6 and IL-10 as rapid diagnostic tools for Gram-negative bacteria and as disease severity predictors in pediatric sepsis patients in the intensive care unit - Zhang, Yunyu; Li, Biru; Ning, Botao (Frontiers in Immunology, 2022)
Background: To explore the diagnostic performance of IL-6 and IL-10 in discriminating gram bacteria types as well as predicting disease severity in ICU-hospitalized pediatric sepsis patients. Method: We retrospectively collected Th1/Th2 cytokine profile in 146 microbiologically documented sepsis patients. Patients were categorized into G+ or G- sepsis group and cytokine levels were compared. Sub-group analysis was designed to eliminate influence of other inflammatory responses on cytokine levels. Results: After propensity score matching, 78 patients were matched and categorized according to gram bacteria types. Compared with G+ sepsis, IL-6 and IL-10 were significantly elevated in G- sepsis (p<0.05). Spearman test proven linear correlation between IL-6 and IL-10 (r=0.654, p<0.001) and their combination indicators (ratio and differences) were effective in identifying G- sepsis. In subgroup analysis, such cytokine elevation was significant regardless of primary infection site. However, for patients with progressively deteriorating organ function (NPMODS), differences of IL-6 and IL-10 levels were less significant between G+/G- sepsis. In the ROC curves of G- sepsis group, AUC for IL-6 and IL-10 was 0.679 (95% CI 0.561-0.798) and 0.637 (95% CI 0.512-0.762), respectively. Optimal cutoff value for diagnosing G- sepsis was 76.77pg/mL and 18.90pg/mL, respectively. While for NPMODS group, AUC for IL-6 and IL-10 was 0.834 (95% CI 0.766-0.902) and 0.781 (95% CI 0.701-0.860). Conclusion: IL-6 and IL-10 are comparably effective in discriminating G+/G- sepsis in PICU. Deteriorated organ function observed in ICU patients reveal that complex inflammatory responses might have contributed to cytokine pattern observed in severe patients, therefore confounded the discriminating efficacy of Th1/Th2 cytokines on predicting gram bacteria types.